Effective tax levels using the Devereux/Griffith methodology. Project for the EU Commission TAXUD/2013/CC/120: Final report - Christoph Spengel; Frank Schmidt; Jost H. Heckemeyer; Katharina Nicolay; Alexandra Bartholmeß; Rainer Bräutigam; Julia Braun; Verena Dutt; Maria Theresia Evers; Christoph Harendt; Oliver Klar; Hannah Nusser; et al. (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
[Introduction] This 2016 report of the project TAXUD/2013/CC/120 presents estimates of the effective tax rates on investment in the EU member states, FYROM and Turkey as well as Norway, Switzerland, Canada, Japan and the United States. The work presented in this report updates for the year 2016 the analyses of the previous projects within the former Framework Contract TAXUD/2008/CC/099 and the current Framework Contract TAXUD/2013/CC/120. Following the methodology used in previous work, we apply the Devereux and Griffith framework to compute effective tax levels. The report considers primarily taxes on corporations in each country, but also includes analyses of personal taxes on investment and saving. It also considers both cross-border investment and investment by small and medium sized enterprises (SME). Background information to the applied model can be found in Devereux and Griffith (1999, 2003), Schreiber et al. (2002) and European Commission (2008, p. 3-54). In addition, the European Commission has recently published studies on the specific impact of interest and inflation rates, tax planning and the debt/equity bias on forward-looking effective tax rates. This report is organized as follows. Section A introduces the tax parameters for the period 1998 - 2016 covered by this report. These tax parameters form the basis of the computations of effective tax rates. Section B provides worked examples for several countries for a better understanding of the model. Section C then provides detailed results for domestic investment in all countries covered in this report. In addition to results focusing on the corporate level, this report comprehensively includes the analysis of personal taxes on investment and saving at the shareholder level for three different types of shareholders when calculating effective tax rates on domestic investment. Section D presents estimates for effective tax burdens of cross-border investment if all countries were either locations of investment or locations of the investor. Finally, Section E provides effective tax burdens of SMEs in selected countries. Please note that all results presented in this report refer to the legal situation as of 1 July 2016.
Keywords: 330; Tax rate; estimate; EU countries; Steuertarif; Schätzung; EU-Staaten